Replacement Nellore heifers receiving supplementation under different herbage allowance: effects on forage characteristics, performance, physiology, and reproduction - Ferreira, I. M. [UNESP]; Homem, B. G.C.; Oliveira, K. A. [UNESP]; Cidrini, I. A. [UNESP]; Abreu, M. J.I. [UNESP]; Batista, L. H.C. [UNESP]; Rodrigues, A. N. [UNESP]; Queiroz, A. C.M. [UNESP]; Bisio, G. H.M. [UNESP]; Prados, L. F. [UNESP]; Moretti, M. H. [UNESP]; Siqueira, G. R. [UNESP]; et al. (Elsevier, 2024)
In Brazil, heifers typically calve at 36–48 months. Due to the high demand for meat and the need to reduce slaughter age, high supplementation has become commonly used in beef cattle farming. However, the literature remains scarce on studies that explore the impact of grazing management during the background phase on the productivity and reproductive efficiency of young Nellore heifers. This study aimed to evaluate the effects of two-herbage allowances (HA) on forage characteristics, performance, physiology and reproductive parameters of replacement Nellore heifers. Ninety weaned heifers [169 ± 19 kg of shrunk body weight (SBW); 210 ± 28 days of age] were blocked by initial BW and randomly assigned to receive different HA: (1) High herbage allowance (HHA: 7.2 kg DM/kg BW) and (2) Low herbage allowance (LHA: 3.3 kg DM/kg BW); and divided into six paddocks, totaling 12 paddocks. The experimental period was divided into the growing phase (D173) and the reproductive season (D83). Continuous stocking with a variable stocking rate was used. The supplement was provided daily with expected intake of around 10 g/kg of BW. The HHA pasture showed greater values of canopy height, greater HA, and lower values of CP and CP: in vitro digestible DM ratio than the LHA pasture over the days of the study (P ≤ 0.05). Herbage mass and the green stem proportion were lower in LHA pasture (P < 0.01), while the green leaf (g/kg DM) and senescent stem proportions (g/kg DM) were higher (P = 0.080) when compared to HHA pasture. Heifers maintained on HHA pasture had a higher average daily gain (P < 0.01), forage intake (P < 0.003), higher SBW (P < 0.01), Longissimus area (P < 0.01), and 12th-rib fat thickness (P < 0.01) than those kept in the LHA pasture. The proportion of heifers that reached the weight at maturity on D173 (P = 0.027) and the proportion of pubertal pregnancy heifers (P = 0.042) were greatest in the HHA treatment. The blood urea nitrogen (P = 0.002) was higher in heifers maintained in the LHA pasture. Heifers maintained in HHA pasture showed higher values of relative abundance of mRNA for UGT1A6 (P = 0.004) and IGFBP3 (P = 0.072). The use of HHA criteria increased forage intake, body gain, and carcass attributes of animals, which led to better reproductive performance of Nellore heifers.
Keywords: Bos indicus; Gene expression; Liveweight gain per area; Replacement heifers; Reproduction